Effects of a 12-week hip abduction exercise program on the electromyographic activity of hip and knee muscles of women with patellofemoral pain: A pilot study - Kelly Mônica Marinho e Lima; Juliane da Silva Flôr; Rafael Inácio Barbosa; Alexandre Márcio Marcolino; Marcela Gomes de Almeida; Danielly Cristina da Silva; Heloyse Uliam Kuriki (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: The purpose of our study was to compare the hip and knee muscle activity before and after a hip abduction exercise program in women with patellofemoral pain (PFP). Methods: Eleven women with PFP were included in our pre/post design study. Participants were assessed before and after 12-week hip abduction exercise program. All participants performed 6 stair climbing repetitions, 3 sets of rope jumps over 30 s and 5 sets of 8 squats to standardize the physical activity level before data collection. We recorded the electromyographic activity from gluteus medius, vastus medialis (VM) and vastus lateralis (VL) for double-legged squat with and without isometric hip abduction. Additionally, participants were asked to perform a step-down test to assess objective function (maximum number of repetitions over 30 s) and completed a clinical evaluation. Results: Longer duration of VM (Mean difference [95% CI]) = -0.97 [-1.48; -0.46], ES [effect size] = 0.66) and VL (-0.81 [-1.35; -0.27], ES = 0.54) were found after the hip abduction exercise program only for free squat. The participants also performed higher number of step-down repetitions (-3.54 [-5.84; -1.25], ES = 1.03) after the hip abduction exercise program and showed improvement in pain reports. Conclusion: A 12-week hip abduction exercise program changed the quadriceps muscle activation pattern and improved pain and objective function of women with PFP. The exercises promoted a longer VM and VL activation duration. Additionally, they promoted a clinical improvement in the patients with PFP.